RANCANG BANGUN MEDIA INFORMASI INTERAKTIF BERBASIS ANDROID SEBAGAI MEDIA INFORMASI PROGRAM STUDI STMIK STIKOM INDONESIA - I Nyoman Agus Suarya Putra; I Dewa Gede Agung Pandawana (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2018)
STMIK STIKOM Indonesia is an IT campus in Denpasar. STMIK STIKOM Indonesia has vision to create a study program which form bachelors of computer science who have ability to make use of smart technology system and digital system to support the development of tourism industry with cultural insight. From direct observation, it was obtained some findings, such as lack of knowledge of marketingship from the performer of the marketing activity of STMIK STIKOM Indonesia about campus life, especially the information about the study program. The effect is lack of knowledge or understanding of the prospective students about the activity done in the process of education in terms of payment, teaching and learning process, up to supporting facilities in STMIK STIKOM campus environment. Most of prospective students have tendency to come to STMIK STIKOM Indonesia to know directly the profile of TI and SK study program rather than only know through information media and its promotion. In the previous research, it has been made the design of information media study program based on desktop, and augmented reality through android application. In the next research, it is developed an information media based on android by combining information system application study program based on desktop with augmented reality which later produce new information media based on android. This new media has advantage with based on android, thus it can be accessed by anyone through android handphone. Interactive multimedia based on android is a proper way to answer the problems. Android technology gives help in the process of presentation about STMIK STIKOM Indonesia. The application that is installed in the students' handphone can inform freely and detail about important information in STMIK STIKOM Indonesia. This modern technology can be downloaded in STMIK STIKOM Indonesia website and can be accessed by the prospective students everywhere they are.